HOST-SPECIFIC ADAPTATIONS OF TOXOPLASMA GONDII: MECHANISMS OF IMMUNE EVASION AND GLOBAL DISTRIBUTION (Spectrum Journal of Innovation, Reforms and Development, 2025)
The most important global protozoan parasite is Toxoplasma gondii, with major relevance for humans and animals. Thus, the current work concerns how T. gondii alters its behavior for specific hosts, the mechanisms it employs to subvert the immune response, and the routes it uses to disperse around the world. Estimates concerning the number of T. gondii strains were based on genetic, immunological, and epidemiologic approaches. The present study was mostly on the Type I, II, and III strains because in the case of Type I, there is a wide genetic diversity at the ROP18 gene itself that is very crucial related to the host's immunity. This happened because it induced higher levels of immunosuppressive cytokines, including IL-10, than the Type II strains or the Type III strains did. The other two strains elicit IFN- γγ, which subsequently leads to production of IL-12: this induces either a balanced immune response or a proinflammatory response. These authors were the first who managed to isolate T. gondii from Elapidae snakes and Boidae birds. Seroprevalence was 35%35% in Elapidae snakes and 25%25% in Boidae. They gave two geneticotypes, the first highly infectious for homeothermic animals and the second generally considered as of low infectiousness. The authors pointed out that the main interest of the study is a high seropositivity for T. gondii in snakes from the traps in French Guiana. Authors of the paper claimed that their isolates were the first to be revived from this species of bird. They documented prevalence of seropositivity in Elapidae at 35%35%, and in Boidae at 25%25%. Two varieties of molecular genetic material are prevalent; the first is considered highly infectious in warm-blooded animals, the second is considered less infectious in general.